Obesity in chronic spinal cord injury is associated with poorer body composition and increased risk of cardiometabolic disease - Nicholas Dietz; Maxwell Boakye; Martin F. Bjurström; Beatrice Ugiliweneza; Shirish Barve; Sriprakash Mokshagundam (Scientific Reports)
Abstract With increased longevity after spinal cord injury (SCI), cardiovascular disease has emerged as a major cause of morbidity and mortality. We evaluate the association of body composition and injury level with cardiometabolic disease (CMD) risk factors. Sixty-two individuals (69% male, 31% female) with chronic SCI (mean duration 7.4, SD ± 5.8 years) were recruited. Mean age of participants was 34.4 ± 12.1 years with BMI of 23.8 ± 5, while 64% had BMI < 25 and 11% >30. Total and percent truncal fat correlated positively (p < 0.05) with serum triglycerides, non-high-density lipid cholesterol, c-reactive protein (CRP), oral glucose tolerance test (OGTT), and measures of insulin resistance. Those with obesity in SCI (defined as BMI ≥ 22) had increased total and trunk mass and fat percentage, unfavorable lipid profiles and evidence of insulin insensitivity. Total fat was associated with CMD risk factors, including insulin resistance (OGTT 60 min r = 0.47, p < 0.05; homeostasis model assessment [HOMA] r = 0.62, p < 0.05), serum triglycerides (r = 0.31, p < 0.05), and inflammation (CRP r = 0.43, p < 0.05). Obesity in SCI related to higher CMD risk, while time since injury and injury level (paraplegia versus tetraplegia) did not. Future studies may evaluate roles of nutrition, exercise, sleep-promotion, and pharmaceuticals to lower neurogenic obesity and chronic CMD risk.